Risk factors of oncogenic HPV infection in HIV-positive men with anal condyloma acuminata in Shenzhen, Southeast China: a retrospective cohort study - Liu, Jiaxin; Yang, Rongqing; Zhao, Xiaobao; Chu, Wenzhu; Li, Dapeng; Wang, Fuxiang; Wei, Lanlan (Frontiers in Public Health, 2023)
Background: HIV-positive patients with anal CA (condyloma acuminata) present an increased risk of anal cancer progression associated with oncogenic HPV infection. It is essential to explore determinants of anal infection by oncogenic HPV among HIV-positive patients with CA.Methods: A retrospective cohort study was performed in HIV-positive patients with CA between January 2019 to October 2021 in Shenzhen, Southeast China. Exfoliated cells were collected from CA lesions and the anal canal for HPV genotype detection by fluorescence PCR. Unconditional logistic regression analysis was used to probe associations of independent variables with oncogenic HPV infection.Results: Among HIV-positive patients with CA, the most prevalent oncogenic genotypes were HPV52 (29.43%), HPV16 (28.93%), HPV59 (19.20%), and HPV18 (15.96%). Risk of oncogenic